PERENCANAAN STRATEGIS SI/TI PADA TOKO “LATINA BAKERY” DENGAN MENGGUNAKAN METODOLOGI WARD AND PEPPARD - Ariati, Nining; Amelia, Rizki; Waty, Rizka; Agnesia, Bella Rizki Dwi; Shela Agustini; Putri Oktariani (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
The development of technology and information systems is currently growing very rapidly, most small, medium, and large organizations and companies have used it to support and facilitate their business processes. “Latina Bakery” is one of the business entities that is currently facing significant challenges in facing increasingly competitive market competition. Latina Bakery has implemented SI/TI to support the success of the store's vision and mission, but in its application, many of the systems used are still not effective and efficient. The main challenges faced lie in two fundamental aspects: First, limitations in the utilization of adequate technological infrastructure, and second, not optimal management and utilization of data to support business decision-making. This condition causes difficulties in adapting and competing amid market dynamics that continue to snowball. To overcome these problems, this research implements the Ward and Peppard methodology, a comprehensive approach consisting of: SWOT analysis (Strengths Weaknesses Opportunities, and Threats), Value Chain Analysis, McFarlan Analysis, and Five Forces Model Analysis. The main objective of this research is to produce an in-depth analysis to formulate an Information Systems and Information Technology (IS/TI) strategy aligned with the vision, mission, and business objectives. It can be a recommendation to move away from the business.